Corn stalk integrity is improved by fungicide combinations containing carboxamide - e Silva, Marina Freitas; Rezende, Wender Santos; Júnior, Domingos da Costa Ferreira [UNESP]; Bueno, Thays Vieira; Agostinho, Flávia Bastos; de Brito, Césio Humberto (FapUNIFESP (SciELO), 2018)
Conservation of vegetative organs, as leaves and stalks, is essential to achieve high maize production. The objective of this work was to evaluate the effects of leaf area maintenance due to fungicides spraying on stalk integrity, its chemical composition and grain yield. The experiment was conducted in Uberlândia – MG, during the second season of 2016. The experiment design was a randomized complete block with six replications and six treatments, representing combinations of fungicides belonging to carboxamide, strobilurin, triazole, and dithiocarbamate chemical groups, and the check treatment (without fungicides). The assessed traits were leaf green area, wet and dry stalk density, stalk breaking strength and height, stalk lignin and cellulose percentage, stalk dry matter, stalk lignin and cellulose content per hectare and grain yield. Treatments containing fungicides, especially the ones containing carboxamide, resulted in higher leaf green area and stalk density. Application of fungicides also increased stalk breaking strength and height; however, no effect was observed on stalk lignin and cellulose percentage. Grain yield, stalk dry matter production, and stalk lignin and cellulose contents per hectare were enhanced by fungicide application, with higher improvements in plants treated with carboxamide. Application of fungicides, mainly when combined with carboxamides, promotes higher maintenance of leaf green area, which leads to improved stalk integrity, higher grain yield, and higher straw production.
Integridade de colmo de milho é melhorada por combinações de fungicidas contendo carboxamida
Keywords: Foliar area; Lignin and cellulose; Straw; Zea mays L